Comparative Study of Gir Cattle and Surti Buffalo Bulls Semen under Middle Gujarat Climate - Chaudhary, P.J.; Dhami, A.J.; Chaudhari, D.V.; Hadiya, K.K.; Patel , J.A. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
This study was undertaken during the favourable breeding season of the year 2016-17 on healthy mature Gir cattle and Surti buffalo bulls, three each, at Sperm Station of the College. The ejaculates (9/bull, total 54) collected in the morning using artificial vagina were evaluated for routine seminal attributes, including acrosomal and plasma membrane integrity. The mean values of ejaculate volume, sperm concentration, mass activity (0-5 score), individual sperm motility, live sperm, abnormal sperm, intact acrosome and HOST reactive sperms observed in fresh semen of Gir cattle and Surti buffalo bulls were 6.20±0.42 and 3.34±0.23 ml (P
Keywords: Gir bulls; Surti bulls; Fresh semen quality; Comparison; Correlations